Malaria-induced ptosis - AlexanderJ. Grosinger (American Journal of Ophthalmology Case Reports, 2021)
Purpose: This study reports two cases of malaria-induced ptosis with surgical resolution. Observations: Case 1 is a 27-year-old female with a past medical history of bilateral ptosis following childhood malaria. Case 2 is a 63-year-old male with left-side ptosis following adult-onset malaria. Both patients required revision surgery but ultimately did well after surgical correction. Conclusions and importance: Malaria-induced ptosis is a rare entity that should be suspected in patients presenting with ptosis following infection and treatment of malaria. It is unknown if the patients’ malaria results from malarial infection, antimalarial treatment, or a combination of both. Surgical correction is the mainstay of treatment.